2010
DOI: 10.1371/journal.pone.0010783
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and Molecular Characterizations of Psychrophilic Fungus Geomyces destructans from New York Bats with White Nose Syndrome (WNS)

Abstract: BackgroundMassive die-offs of little brown bats (Myotis lucifugus) have been occurring since 2006 in hibernation sites around Albany, New York, and this problem has spread to other States in the Northeastern United States. White cottony fungal growth is seen on the snouts of affected animals, a prominent sign of White Nose Syndrome (WNS). A previous report described the involvement of the fungus Geomyces destructans in WNS, but an identical fungus was recently isolated in France from a bat that was evidently h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
103
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 102 publications
(109 citation statements)
references
References 52 publications
5
103
1
Order By: Relevance
“…1A). The diversity of hydrolytic enzymes present is consistent with previous reports of multiple hydrolytic activities in P. destructans cultures, although the proteins responsible for these activities were not determined (21,22). Many of these enzymes are likely to play a role in saprophytic growth, but peptidases have also been identified in the secretomes of the human pathogens C. albicans and Aspergillus fumigatus (23,24), where they mediate host-pathogen interactions (14,15).…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…1A). The diversity of hydrolytic enzymes present is consistent with previous reports of multiple hydrolytic activities in P. destructans cultures, although the proteins responsible for these activities were not determined (21,22). Many of these enzymes are likely to play a role in saprophytic growth, but peptidases have also been identified in the secretomes of the human pathogens C. albicans and Aspergillus fumigatus (23,24), where they mediate host-pathogen interactions (14,15).…”
Section: Resultssupporting
confidence: 87%
“…Connective tissue, vascular structures, and muscle fibers are degraded during infection, suggesting that hydrolytic enzymes are used by the invading pathogen (27). Secreted hydrolytic activities have been described by monitoring growth of P. destructans on a wide range of in vitro substrates (21,22), but the fungal proteins responsible for these activities have not been elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Pseudogymnoascus destructans is the fungal causal agent of WNS [5]. Pseudogymnoascus destructans is a psychrophile, well-adapted to growing at 4°-15°C, and widely distributed in the caves and mines that serve as bat hibernacula [58]. Bats infected with P. destructans exhibit histopathological lesions on wings and other body parts, are frequently aroused from hibernation-induced torpor, and possibly succumb to WNS due to fat depletion and starvation [911].…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent studies indicated that the cottony appearance was due to fungal growth. The extensive fungal colonization of bat skin and hair, characteristic histopathological appearance, and exclusive presence of a specific fungal DNA in the animals' tissues led to the discovery of the causal agent-a newly described species called Geomyces destructans [2][3][4][5][6]. Subsequent studies revealed that this condition has caused the deaths of nearly a million bats in the Northeast and it has rapidly spread to other parts of the country [7].…”
mentioning
confidence: 99%
“…Accordingly, this disease can be confirmed by the morphological appearance of the fungus on any part of the body, histopathology of affected tissues with demonstration of hyphae-conidia, or demonstration of G. destructans by PCR-nucleotide sequencing [3,4,6,11]. Thus, it is reasonable to conclude that WNS is neither an exclusive presentation nor an all-encompassing description of G. destructans infections in bats.…”
mentioning
confidence: 99%